Celiac disease in patients having recurrent aphthous stomatitis - Selim AYDEMİR and Nilgün SOLAK TEKİN and Erol AKTUNÇ and Gamze NUMANOĞLU and Yücel ÜSTÜNDAĞ (Turkish Journal of Gastroenterology, 2019)
-